Obszary Rezonansowe Drugiego Rodzaju przy Obciążeniu Śledzącym - Piszczek, K. (Engineering Transactions, 1961)
E. METTLER’s method constituting an effective asymptotic method for determining resonance regions is generalized to the case where the load direction is fixed to the body thus following its deformations. The parametric resonance of the second kind is considered. This resonance may take place in the neighbourhood of the angular frequency θ = |Ω1- Ω2/k of the excitation. The damping is disregarded.